STUDENTS' PERCEPTION OF SIPINTAR SAVINGS PRODUCTS (STUDENT EDUCATION SAVINGS) AT BANK KERINCI - Mi Iswari, Dela; Bustami, Yuserizal; Desiana, Desiana; Melani, Zahaqi (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2024)
SIPINTAR savings product is a savings product issued by Bank Kerinci specifically for students. This study aims to determine the system and procedure of SIPINTAR savings products and students' perceptions of SIPINTAR savings products at Bank Kerinci. The type of research used is descriptive quantitative research with a survey approach. The number of samples in this study was 76 respondents who were students of SMPN 1 Kerinci. The data was analyzed using perceptual analysis with the help of SPSS version 23. The results showed that SIPINTAR savings procedures consist of 3, namely account opening, deposit, and withdrawal; two service systems are coming directly to the office and shuttle services. Students' knowledge of SIPINTAR savings products is adequate; this is shown by students' responses to statements in the questionnaire that predominantly voted strongly agree and agree